Interface and surface analysis for pharmaceutical applications: challenges and recent advances - Piggott, Matthew John; Zelzer, Mischa (Tekno Scienze, 2014)
Innovation in R&D is a key target for the pharmaceutical sector to address some of the challenges it currently faces. This review discusses these challenges in the context of pharmaceutically relevant surfaces and interfaces. The surface properties of materials determine many pharmaceutically important interactions and can be drastically different from the material’s bulk properties. We first introduce current challenges in the surface and interface analysis of pharmaceutical materials in the context of material design, administration and fabrication. We then review recent scientific and technological advances aimed to address these issues and discuss examples that illustrate the capabilities of these techniques.